THE IDEOLOGY OF UNIVERSITY STUDENTS TOWARDS POLITICAL DISCOURSE IN SATELLITE CHANNELS: A field study on media students at Al-Mustansiriya University - Mohammad, Ghazwan Jabbar (ALBAHITH ALALAMI, 2020)
‏The speech delivered by political blocs and parties and broadcasted by satellite channels, social and communication media has different ideologies and orientations: moderate speech calling for calm or one raising crises.‏The latter is considered very challenging due to its local and international reference.‏, this paper aims at uncovering these challenges especially during the political crisis witnessed in Iraq. This paper sheds light on the most important crisis that spread in public opinion, broadcasted by satellite, and raised by politicians who are competing to gain authority leading to a lack of peoples, confidence in them.‏This matter should not be neglected at all; especially in Iraq which is witnessing the birth of new democracy after years of dictatorship.Is it moderate convulsive, crisis-provoking, calls for calm, or escalating? Do Iraqi citizens trust the politicians, ability to solve the political crisis?‏The researchers diagnosed the faults in the political speeches directed to the Iraqi public through satellite channels in different circumstances, especially during the repetitive political crisis in Iraq, and caused by the language of escalation interested in politicians, speeches that aim to adopt a moderate speech and end political disputes cris.The main conclusion is:* Political discourse channeled through satellite channels provides an opinion to the public about various political events and crises.*  The public believes that politicians are seeking, through their speeches, to cause crises in Iraq.* ‏The Iraqi public prefers a moderate speech that may contribute to stabilizing the situation.